Implication of the root growth and soil macropores distribution on sugarcane yield in Takalar, Indonesia - Safitri, Wina; Ala, Ambo; Gusli, Sikstus; Salim, Iqbal (Journal of Degraded and Mining Lands Management, 2024)
This study examined the relationship between the decline in sugarcane productivity and the distribution of macropores and depth of root penetration in sugarcane plantations in Takalar during one planting period (October 2021-September 2022). There were five observation points (P1, P2, P3, P4, and P5) in one hectare of land to measure the distribution of soil macropores using methylene blue solution. Cross-sections of the soil were made to observe the presence of plant roots at a depth of 0-40 cm with a width of 60 cm. In each plot, disturbed soil samples were collected to measure soil texture, soil organic matter (SOM), nitrogen (N), phosphorus (P), and potassium (K) contents. Other measurement parameters were the infiltration rate and plant productivity. The results indicated that SOM and NPK levels at the research location were deficient, serving as the first indicators of problematic soil. Macropore observations revealed that macropores were distributed only at a less than 10 cm soil depth. This distribution limited the penetration of plant roots to a depth of   0-40 cm. The root length density (RLD) value indicated the absence of roots at depths of 30-40 cm in plots P2 and P3. The field findings explained why sugarcane production in Takalar only achieved 50%, around 40 t ha-1 from the first ratoon sugarcane harvest, instead of the expected 70-80 t ha-1.